Developing a Decision Support Tool to Guide Shared Decision‐Making in Bipolar Depression Treatment: Results From a Collaboration Between Clinicians and People With Lived Experience - Fuentes‐Salgado, Manuel; Gardea‐Resendez, Manuel; Smith, Andrew; Lam, Angie; Allen, Kimberly; Ercis, Mete; Kremin, Ashley; Joyce, Jeremiah B.; Park, Jin Hong; Keeth, Nicola; Moore, Katherine; Betcher, Hannah; et al. (Bipolar disorders, 2025)
ABSTRACT Objective To build consensus from different stakeholders on the content and digital interactivity of a shared decision making (SDM) tool to guide patient‐clinician collaborative conversations about treatment for bipolar depression. Patients and Methods This study was conducted between September 2022 and September 2023. In the first phase, we conducted a narrative review on pharmacological, neuromodulatory, and psychotherapeutic treatments available for bipolar depression. For each option, we assessed treatment effectiveness, side effects, need for clinical monitoring, clinical considerations, and cost. In the second phase, committees comprised of mental health clinicians and people with lived experience with bipolar disorder from a national mood disorders advocacy group identified key features and content to be included in the SDM tool. A thematic analysis of these data then contributed to populate the SDM tool. Results Twenty‐one evidence‐based treatment options identified from the narrative review were presented to the four convened committees (clinical, lived experience, peer council, and integrated steering committees) in five meetings. After discussions and thematic analysis, 12 outcomes of interest for each of the therapeutic interventions were delineated for inclusion in a web‐based SDM tool. A detailed description of the development process and SDM tool is provided. Conclusion This is the first partnership between clinicians and persons with bipolar disorder lived experience charged with the development of a patient‐centered SDM tool to integrate clinical evidence with real‐world clinical practice and patient preferences for use during clinical encounters. Human‐centered design and testing in real clinical encounters will now contribute to refining the instrument and readying it for rigorous evaluation and implementation in practice.